2012
DOI: 10.1021/bi201721r
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 gp41 Transmembrane Domain Interacts with the Fusion Peptide: Implication in Lipid Mixing and Inhibition of Virus–Cell Fusion

Abstract: Fusion of the human immunodeficiency virus (HIV) with target cells is mediated by the gp41 subunit of the envelope protein. Mutation and deletion studies within the transmembrane domain (TMD) of intact gp41 influenced its fusion activity. In addition, current models suggest that the TMD is in proximity with the fusion peptide (FP) at the late fusion stages, but there are no direct experimental data to support this hypothesis. Here, we investigated the TMD focusing on two regions: the N-terminal containing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
68
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 90 publications
11
68
0
Order By: Relevance
“…Importantly, experiments performed with the intact virus demonstrated that a mutant in which the GxxxG motif within the TMD in the HXB2 envelope was altered, was defective in fusion (58). Furthermore, the FP and the TMD of HIV-1 heteroassemble in the membrane and synergize in inducing membrane fusion (55). A similar observation was previously demonstrated in the influenza virus, in which TMD-FP interactions were shown to play a key role in the fusion cascade (59).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Importantly, experiments performed with the intact virus demonstrated that a mutant in which the GxxxG motif within the TMD in the HXB2 envelope was altered, was defective in fusion (58). Furthermore, the FP and the TMD of HIV-1 heteroassemble in the membrane and synergize in inducing membrane fusion (55). A similar observation was previously demonstrated in the influenza virus, in which TMD-FP interactions were shown to play a key role in the fusion cascade (59).…”
Section: Discussionsupporting
confidence: 67%
“…gp41 TMD (FIMIVGGLVGLRIVFAVLSIV) is also highly conserved within different strains of HIV (53) and was suggested to play several roles during HIV-1 cell fusion, including anchoring the envelope glycoprotein to both viral and cellular membranes (54), assisting in the oligomerization of gp41 (55), inducing phospholipid vesicle fusion (55,56), promoting cell-cell fusion (57,58), and immunosuppressing T-cell activation (30). Importantly, experiments performed with the intact virus demonstrated that a mutant in which the GxxxG motif within the TMD in the HXB2 envelope was altered, was defective in fusion (58).…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that formation of this trimeric state may be initiated by interactions between the polar segments of the NHR (S546-N554) and CHR (E647-K655) regions, which lack high membrane affinity but make tight and specific interhelical contacts in the 6HB. Specific interactions between the FP and TM (35), which are only accessible after formation of the fusogenic prebundle, may further stabilize formation of the postfusion state. Competition between intermolecular and membrane association may also be impacted by a shift in lipid composition after outer leaflet lipids of the viral and host cells can mix with one another by translational diffusion through the hemifusion stalk, which would be a slow and strongly temperature-dependent process.…”
Section: Discussionmentioning
confidence: 99%
“…For example, self-assembly of paramyxovirus (43,44), influenza virus (45,46), and HIV (47) F-protein transmembrane domains was demonstrated experimentally and is considered a determinant for proper protein folding and fusion activity (44,47). Studies with class I vFMGs have shown that insertion of synthetic, soluble fusion peptides into the membrane can deform the lipid bilayer (48) and induce membrane fusion (49).…”
Section: Discussionmentioning
confidence: 99%